The Politics of Deforestation in Africa Madagascar, Tanzania, and Uganda - Horning, Nadia Rabesahala (Springer International Publishing, 2018)
This book explores how environmental policies are made and enforced in Africa. Specifically, this project explains the gap between intent and impact of forest policies, focusing on three African societies facing persistent deforestation today: Madagascar, Tanzania, and Uganda. The central claim of the study is that deforestation persists because conservation policies and projects, which are largely underwritten by foreign donors, consistently ignore the fact that conservation is possible only under limited and specific conditions. To make the case, the author examines how decision-making power is negotiated and exercised where communities make environmental decisions daily (local level) and where environmental policies are negotiated and enacted (national level) across three distinct African political systems. Nadia Rabesahala Horning is Associate Professor, Director of African Studies, and Faculty Director of Social Entrepreneurship at Middlebury College, USA.